Quality engineering techniques : an innovative and creative process model - Rostamkhani, Ramin; Karbasian, Mahdi (Boca Raton : CRC Press, 2020)
"This book provides instructions to enhance productivity and sustainability by using Quality Engineering Techniques (QET) in statistical and non-statistical projects. It presents an integrated format for better management of traditional processes in industrial factories"--
OCLC-licensed vendor bibliographic record.
Keywords: Quality control; Industrial management; Project management; TECHNOLOGY / Manufacturing; MATHEMATICS / Probability & Statistics / General